The Influence of Active Gaming on Cardiorespiratory Fitness in Black and Hispanic Youth. (10th September 2018) - Flynn, Rachel M.; Staiano, Amanda E.; Beyl, Robbie; Richert, Rebekah A.; Wartella, Ellen; Calvert, Sandra L.
ABSTRACT: BACKGROUND: Youth in the United States have low levels of cardiorespiratory fitness, a risk factor for childhood obesity. Lower levels of physical fitness for black and Hispanic youth contribute to health disparities. In this feasibility study, we examined active video games (AVGs) as a tool to improve fitness and attitudes toward physical activity during early adolescence. METHOD: A 6‐week AVG program took place in a youth development program in a high‐poverty neighborhood in New York City. Youth aged 10 to 15 years (50% overweight or obese) participated in 2 fitness tests and completed surveys that captured barriers to physical activity pre‐ and postintervention. Each week, participants played Wii Fit games for 30 minutes. RESULTS: Participants improved the number of sit‐ups and step‐ups they completed from pre‐ to postintervention (p < .05). Participants also increased their self‐efficacy, intention to exercise and perceived social support to exercise (p < .05). Youth reported a high level of enjoyment and perceived Wii Fit as ways to increase physical fitness and increase their physical activity. CONCLUSION: AVGs may be a viable alternative exercise program to increase physical activity for black and Hispanic youth living in poverty‐impacted neighborhoods.